OP0293 USE OF WHOLE-BODY MAGNETIC RESONANCE TO IDENTIFY POTENTIAL DIAGNOSTIC CLUES IN CHILDREN WITH FEVER OF UNKNOWN ORIGIN (FUO). (2nd June 2020) - Signa, S.; Caorsi, R.; Stagnaro, G.; Minoia, F.; Picco, P.; Ravelli, A.; Damasio, M. B.; Gattorno, M.
Abstract : Background: Whole-body magnetic resonance imaging (WBMRI) is a fast and accurate method to detect diseases throughout the entire body without exposure to ionizing radiation. Possible emerging applications for this technique include rheumatologic field and evaluation of fever of unknown origin (FUO). Objectives: To evaluate the ability of WBMRI to identify significant potential diagnostic clue (PDC) in patients presenting a non specific inflammatory clinical picture. Methods: We retrospectively collected cases of pediatric patients followed in a single pediatric rheumatology center who underwent WBMRI between January 2010 and December 2015 for the following indications: i) FUO (temperature greater than 38.3°C for more than three weeks or failure to reach diagnosis after one week of investigations), iii) recurrent fever (febrile episodes separated by periods of normal temperature), iii) Inflammation of unknown origin, IUO (an illness of at least 3 weeks' duration, with raised inflammatory markers and fever below 38.3°C).WBMRI studies were acquired with coronal and sagittal planes (slice thickness 5mm) with acquisition of several image sets with automatic direct image realignment after acquisition creating a whole-body scan.Sequences include short τ inversion recovery (STIR) and T1-weighted. All studies have been evaluated twice, the second time according to a predefined checklist, defined by an experienced radiologist, considering systematically single /multifocal bone lesion, bone marrow, joint effusion, soft tissues, adenopathies, parenchymal and vessels looking for PDC. We considered as a Potential Diagnostic Clue each alteration of the examined district that can potentially guide the diagnosis. Each alteration found is a PDC. We retrospectively evaluated patients' clinical history and final diagnosis and we classified the PDCs identified during both first evaluation and re-evaluation as: Not useful (the identified PDC did not guide the diagnosis and is not coherent with the final diagnosis), consistent (the identified PDC is congruent with the patient's final diagnosis) or diagnostic (the identification of the considered PDC strongly orient the final diagnosis). Results: We collected 104 patients who underwent WBMRI; 24 (23%) of them presenting FUO, 28 (27%) presenting recurrent fever and 52 (50%) presenting IUO. The mean age of onset symptoms was 6 years and nine months (range: 2 weeks old- 17 years and 6 months). The mean age of execution of WBMRI was 9 years (range: 5 months old- 19 years). After the whole diagnostic work-out a final diagnosis was achieved in 44 patients (42%).PDCs were identified at the first evaluation in 78/104 cases (75%). In 22 cases (21%) the identified PDCs were consistent with the diagnosis, whereas in 9 cases (8.5%) the identified PDCs were considered diagnostic. Globally we can consider that at first evaluation PDCs were somehow contributory to the diagnosis in 31 cases (30%; 6 JIA, 7 systemic infections, 5 monogenic inflammatory diseases, 4 ALPS, 2 Goldbloom's Syndrome, 2 Vasculitis, 1 eosinophilic fasciitis, 1 hystiocytosis, 3 oncologic diagnosis).Blind re-evaluation of WBMRI allowed the identification of additional PDCs in 52 patients (12 of them previously negative). In 10 cases the PDC found after re- evaluation were consistent with the final diagnosis (2 JIA, one infectious disease, one neuroblastoma, 3 ALPS, 1 monogenic inflammatory disease, 1Takayasu arteritis, 1 Goldbloom's syndrome). Conclusion: WBMRI can be a powerful diagnostic tool in patients with FUO. A predefined checklist increases sensitivity of WBMRI in the identification of PDC. Disclosure of Interests: Sara Signa: None declared, Roberta Caorsi: None declared, Giorgio Stagnaro: None declared, Francesca Minoia: None declared, Paolo Picco: None declared, Angelo Ravelli: None declared, Maria Beatrice Damasio: None declared, Marco Gattorno Consultant of: Sobi, Novartis, Speakers bureau: Sobi, Novartis